Endothelial derived, secreted long non-coding RNAs Gadlor1 and Gadlor2 aggravate cardiac remodeling - Keles, Merve; Grein, Steve; Froese, Natali; Wirth, Dagmar; Trogisch, Felix; Wardman, Rhys; Hemanna, Shruthi; Weinzierl, Nina; Reiners-Koch, Philipp-Sebastian; Uhlig, Stefanie; Lomada, Santosh K.; Dittrich, Gesine M.; et al. (Molecular therapy. Nucleic Acids, 2024)
Pathological cardiac remodeling predisposes individuals to developing heart failure. Here, we investigated two co-regulated long non-coding RNAs (lncRNAs), termed Gadlor1 and Gadlor2, which are upregulated in failing hearts of patients and mice. Cardiac overexpression of Gadlor1 and Gadlor2 aggravated myocardial dysfunction and enhanced hypertrophic and fibrotic remodeling in mice exposed to pressure overload. Compound Gadlor1/2 knockout (KO) mice showed markedly reduced myocardial hypertrophy, fibrosis, and dysfunction, while exhibiting increased angiogenesis during short and prolonged periods of pressure overload. Paradoxically, Gadlor1/2 KO mice suffered from sudden death during prolonged overload, possibly due to cardiac arrhythmia. Gadlor1 and Gadlor2, which are mainly expressed in endothelial cells (ECs) in the heart, where they inhibit pro-angiogenic gene expression, are strongly secreted within extracellular vesicles (EVs). These EVs transfer Gadlor lncRNAs to cardiomyocytes, where they bind and activate calmodulin-dependent kinase II, and impact pro-hypertrophic gene expression and calcium homeostasis. Therefore, we reveal a crucial lncRNA-based mechanism of EC-cardiomyocyte crosstalk during heart failure, which could be specifically modified in the future for therapeutic purposes.
Online verfügbar: 15. August 2024, Artikelversion: 30 August 2024
Gesehen am 30.10.2024